Maternal postnatal depression and offspring depression at age 24 years in a UK-birth cohort: the mediating role of maternal nurturing behaviours concerning feeding, crying and sleeping - Culpin, I; Hammerton, G; Bornstein, MH; Heron, J; Evans, J; Cadman, T; Sallis, HM; Tilling, K; Stein, A; Kwong, ASF; Pearson, RM (F1000Research, 2021)
Background: Maternal postnatal depression (PND) is a risk factor for offspring depression in adulthood. However, few longitudinal studies have examined the role of maternal nurturing parenting behaviours in the association between maternal PND and offspring depression in adulthood. Methods: We examined pathways from maternal PND measured using self-reported Edinburgh Postnatal Depression Scale at 8 weeks to offspring ICD-10 depression diagnosed using the Clinical Interview Schedule-Revised computerised assessment at 24 years through maternal-reported nurturing behaviours concerning feeding, sleeping and crying measured from pregnancy to age 3 years 6 months in 5,881 members of the UK-based birth cohort study, the Avon Longitudinal Study of Parents and Children. Results: The fully adjusted model revealed an indirect effect from PND to adult offspring depression through the combination of all parenting factors (probit regression coefficient [B]=0.038, 95% confidence interval [CI] 0.005, 0.071); however, there was no evidence of a direct effect from early maternal PND to offspring depression once the indirect effect via parenting factors was accounted for (B=0.009, 95%CI -0.075, 0.093). Specificity analyses revealed indirect effects through maternal worries about feeding (B=0.019, 95%CI 0.003, 0.035, p=0.010) and maternal perceptions and responses to crying (B=0.018, 95%CI 0.004, 0.032, p=0.012). Conclusions: The adverse impact of maternal PND on offspring depression in early adulthood was explained by maternal nurturing behaviours concerning feeding, crying and sleeping in early childhood. Residual confounding and measurement error likely limit reliable conclusions. If found causal, interventions providing support to reduce worries around maternal nurturing behaviours and treating depression could reduce adverse outcomes in adult offspring of depressed mothers.